Study on mosaicism of SCN1A gene mutation in parents of children with Dravet syndrome - Liu, AJ; Yang, XX; Xu, XJ; Wu, QX; Tian, XJ; Yang, XL; Wu, XR; Wei, LP; Zhang, Y. H. (Zhonghua er ke za zhi= Chinese journal of pediatrics, 2017)
Objective: To investigate the clinical phenotypes and the mutant allele proportion of parents with SCN1A gene mutation mosaicism of Dravet syndrome (DS) children, thus to provide guidance for family reproduction and prenatal diagnosis. Method: The clinical data and peripheral blood DNA samples of DS patients with a SCN1A gene mutation proved by Sanger sequencing were collected prospectively from February 2005 to November 2016 in Department of Pediatrics, Peking University First Hospital. The same mutation was searched in parents and other available relatives. Parental somatic mosaicism was confirmed and quantified by Ion Torrent Personal Genome Machine (PGM) and Raindrop droplet digital PCR (ddPCR). The families were followed up and prenatal diagnosis was provided. Result: Mosaicisms of SCN1A gene mutation in parents were identified in 5.2% (30 out of 575) DS families. Seventeen were fathers and thirteen were mothers. The mutant allele proportion ranged from 1.7% to 32.9% by PGM and from 0.82% to 34.51% by ddPCR, respectively. In 30 parents with somatic mosaicism, thirteen were asymptomatic, ten had a history of febrile seizures (FS), five with epilepsy, one with febrile seizure plus and one had a history of afebrile seizure. Four families had two children with DS. Three siblings of the probands were confirmed genetically with the same pathogenic mutation. One deceased sister of the proband was assumed to have the same pathogenic mutation because she matched DS diagnosis after medical history review despite no blood sample. Two families received prenatal diagnosis. One second pregnancy was terminated because the fetus inherited the mutation as the mother's wish. Conclusion: Sanger sequencing detects parents of some children with DS are SCN1A mutation mosaics. PGM and ddPCR can be used for accurate quantification of mutant mosaics, which can provide accurate guidance for family genetic counseling.